Pengembangan Aplikasi Android Menggunakan REST API dengan Metode Waterfall Untuk Peningkatan Aksesibilitas Situs Repositori - Setiawan, Muhhamad Ajun; Avianto, Donny (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
The repository system offered by the campus to students to increase students' interest in reading, in fact, is still low in use even in an academic environment. This happens because the repository system offered is less convenient for students to use as a literacy tool. The result of the research is an application that is expected to be able to improve accessibility to repositories. A data filter feature and a new display update for the repository system will be added by the author in the implementation. Users of this service can filter their search results depending on the field of study, research specialization, and research period. Usability testing on the created application has shown that many students will start to be interested in using the repository system as their literacy material. This test used the System Usability Scale methodology, where the users of the program - in this case, university students - were given a questionnaire. According to the results obtained in the questionnaire, the usability value was quite high at 75.63 percent. The conclusion is that the repository application developed with the addition of this filtering feature can increase literacy interest in students.